The role of IS in the covid-19 pandemic: A liquid-modern perspective. (December 2020) - Doyle, Ronan; Conboy, Kieran
Highlights: The pandemic and technologies are catalysing fundamental change. Introducing a selection of 'liquid modernity' theoretical principles. All pandemic control methods are potentially counterproductive. Big data will not order a safe path out of the pandemic crisis. Information privacy regulations are irrelevant when circumvented. Abstract: History shows that pandemics can catalyse enormous change, fundamentally transforming the way people make sense of the world. Technologies can also be catalysts of change. While digital technologies are playing a vital role in tackling the covid-19 pandemic, the pandemic also presents a significant opportunity for digital technologies. Some experts believe the pandemic may permanently normalise the comprehensive societal use of digital technologies. This article casts a critical eye over the potential implications of this opportunity in the context of information systems (IS) research and development. We introduce and outline selected principles of Zygmunt Bauman's theory of liquid modernity. We then apply the liquid-modern principles to illustrative examples drawn from the covid-19 literature by focussing on three areas of established information systems interest: control, big data and information privacy. We show that traditional conceptualisations of scientific and societal order and control need to be reassessed; that big data alone cannot order clear and safe paths out of the current crisis and that information privacy regulations are irrelevant when undermined or circumvented by public and private actors. We conclude by making four recommendations for IS pandemic researchers and five practical recommendations in the context of the pandemic.